PERANCANGAN BRAND IDENTITY ADRISTHA TOUR & TRAVEL DI BADROOM STUDIO DENPASAR - Albar, Seifi Yusila; Wibawa, Arya Pageh; Wirawan, I Gusti Ngurah (AMARASI: JURNAL DESAIN KOMUNIKASI VISUAL, 2024)
Adristha Tour & Travel is a startup in the travel agency sector, established in 2024 in Denpasar, Bali. The designing a brand identity for Adristha Tour & Travel, in collaboration with Badroom Studio, aims to create a competitive image and positioning in the tourism industry. As part of the tourism industry on a tourist island with intense business competition, Adristha Tour & Travel needs a strong brand identity to compete with its competitors. The objective of designing this visual brand identity is to promote and enhance brand awareness among the audience. This research employs a qualitative method through observation and discussions with senior graphic designers at Badroom Studio. The design process includes concept development through brainstorming and brandbrieff creation, design execution, and implementation on relevant media. The result of this design is a visual brand identity that reflects the vision, mission, and image of Adristha Tour & Travel as a professional and trustworthy company. Visual elements such as the logo, color palette, and typography with a clean and corporate-related style are also designed to support the creation of a strong and consistent visual identity.